(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
There is a difference between considering performances as occurrences that happen in one place and recognizing them as triggers of territorialities. The purpose of this research was to analyze performative experiences conceived in Cuba, Brazil and Mexico that established feminist debates through the subversion of territorialities given a priori and their power relations. The objective was to blur hierarchical dichotomies between public and private spaces, artist and spectator, scene and political manifesto, individuality and collectivity.